Kuzeybatı Anadolu'da (Kıyı Troas Bölgesi) kırsal hayvancılık ve arazi kullanımı: Etnoarkeolojik bir bakış - Özdemir, Abdulkadir; Bamyacı, A. Onur (My University, 2019)
Özet: Son yıllarda günümüzde yaşanılan ya da yakın zamanda terk edilmiş kırsal yerleşmeleri kapsayan etnografik araştırmalar, arkeolojik araştırmaların ilgi çekici bir alanı haline gelmiştir. Bu çalışma modern materyal kültür kalıntıları üzerinde arkeolojik hipotezler için etnografik açıdan incelemeyi amaçlamıştır. Çanakkale’nin Kıyı Troas bölgesinin kırsal karma ekonomik aktiviteleri arasında hayvancılık ön plana çıkmaktadır. Bugün hâlâ kullanılmaya devam eden bölgeye has hayvan ağılları gibi etnografik veriler ışığında, aynı coğrafyada ve benzer çevresel etkenler karşısında, bölge insanının Prehistorik dönem toplulukları ile benzer arazi kullanım alışkanlıkları ve üretim tekniklerini sürdürdükleri düşünülmektedir. Bölgenin yakın geçmişine ait kırsal arazi kullanımı, kırsal ekonomik unsurlar ve geleneksel üretim süreçlerine ait etnografik verilerin, arkeolojik problemlerin çözümüne katkı sağlayacağı göz önüne alındığında, Troas kıyı bölgelerinde yer alan hayvancılık ile ilgili yapıların ve ekonomik faaliyet alanlarının etnografik yöntemlerle incelenmesi, aynı bölgede yaşayan prehistorik köy toplumların geçim ekonomilerini anlama konusunda fikirler sunabilir. Abstract: In recent years, ethnographic research, which includes modern pastoral sites or recently abandoned, has become a curious field of archaeological research. The aim of this study was to investigate the modern material culture ethnographically as a source of archeological hypotheses about the past behaviors. Rural mixed economic activities at the coastal Troad region of Çanakkale are mainly dominated by stock-breeding. In the light of the ethnographic data such as the animal-related structures that still continue to be used today, in the same area and similar environmental factors, it is thought that the people of the region continue their similar economic exploitation of the rural land use habits like as prehistoric communities. Considering that the ethnographic data on rural land-use, rural economic factors and traditional agrarian practices of present-day behavior will contribute to our understanding of past mode of the rural economy of prehistoric societies.

In recent years, ethnographic research, which includes modern pastoral sites or recently abandoned, has become a curious field of archaeological research. The aim of this study was to investigate the modern material culture ethnographically as a source of archeological hypotheses about the past behaviors. Rural mixed economic activities at the coastal Troad region of Çanakkale are mainly dominated by stock-breeding. In the light of the ethnographic data such as the animal-related structures that still continue to be used today, in the same area and similar environmental factors, it is thought that the people of the region continue their similar economic exploitation of the rural land use habits like as prehistoric communities. Considering that the ethnographic data on rural land-use, rural economic factors and traditional agrarian practices of present-day behavior will contribute to our understanding of past mode of the rural economy of prehistoric societies.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Kuzeybatı Anadolu; Etnoarkeoloji; Hayvancılık; Kırsal arazi kullanımı; Hayvan ağılları; Northwestern Anatolia; Ethnoarchaeology; Stock-breeding; Rural land-use; Animal-related structures